WOMEN AND POLITICS: A CASE STUDY ON WOMEN’S POLITICAL CHOICE IN MAKASSAR CITY, MAROS AND GOWA DISTRICTS - Kambo, Gustian Anwar (ISJN Journal, 2019)
This study aims to understand the complexity of the dynamics of women's behavior in choosing which is tangible in their participation in female legislative candidates. Women's participation in politics is a reflection of the existence of justice in democracy which is now being tried to be realized in the transition period. The aspect of women's participation in democracy is not something that comes suddenly but requires awareness and care of all our society, especially for women themselves. The results of the study indicate that women's behavior shown in their political choices in the General Election reflects a rather weak participation, presented by women themselves. In this case, women's political choices are not only based on their desire to choose women themselves, but also based on other factors, such as pressure from the family, friends and even the electoral party. Although it is not generally applicable to all elements of women in this way, it shows that at least women's participation in voting is still not considered in the conventional form.